Dental students' knowledge of and attitudes towards prescribing medication in Western Australia. (22nd April 2022) - Park, Joon Soo; Daniel, Ben K.; Wong, Pauline Y.; Abbott, Paul V.; Ngo, Hien C.
Abstract: Introduction: Dentists can prescribe medications for prophylactic and therapeutic purposes. In Australia, dental graduates can autonomously practise within the scope of their qualifications without needing to undertake an internship post‐graduation. Although previous research has identified knowledge gaps amongst dental students in Australia on pharmacology and pharmacotherapeutic knowledge, there has been no published research that qualitatively highlights dental students' knowledge of medication prescribing in Australia. This study aimed to undertake a qualitative analysis of Western Australian dental students' attitudes towards and knowledge of medication prescribing. Methods: This qualitative case study design employed semi‐structured interviews as means of collecting data. It utilised a purposive sampling in penultimate and final year dental students at the University of Western Australia. Results: Twenty dental students participated in the study. Five key themes were identified in the data: current and previous education, application when delivering pharmacology and pharmacotherapeutics, teaching to ensure patient‐centred care, supervision and referral to relevant resources. Participants agreed that having previous knowledge in the area provides students with confidence regarding medication prescribing. Furthermore, students in this study valued having guidance when prescribing medications. Conclusions: This study highlights the complexity of medication prescribing for dental students. It also highlights their experience with the current pharmacology and pharmacotherapeutics curriculum. All students interviewed valued application‐based teaching, making it specific to dentistry. If curriculum were to be redeveloped, considering their perceptions may be a valuable tool.